Rekonseptualisasi Nasionalisme Pemuda Indonesia dalam Era Digital: Reconceptualization of Indonesian Youth Nationalism in the Digital Era - Adi, Anggun Putri; Dwi Rizky Wulan Maulida; Lisa Aziza Rohman (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
The social phenomenon with the hashtag #kaburajadulu which is widely discussed on social media, shows the tendency of Indonesian youth to seek work or education abroad to improve their economic conditions. This hashtag has turned into an informal movement that spreads information about job opportunities, education, and the legal process to go abroad which is considered a path to prosperity. Advances in digital technology are increasing its pace, while also triggering debates about nationalism. This article aims to see how much nationalism is possessed by the youth who realize the hashtag #kaburajadulu amidst the difficulty of finding employment in Indonesia. Based on Anderson's perspective, nationalism is a construction formed through language, media, and symbols that are used together. This study uses a qualitative method with a phenomenological approach, through literature studies and interviews. The findings show that although many youth are involved in this trend, they still have a spirit of nationalism and are committed to contributing to Indonesia after returning from abroad.